Impact of AT2-receptor stimulation on vascular biology, kidney function, and blood pressure - Danyel LA; Schmerler P; Paulis L; Unger T; Steckelings UM (Dove Medical Press, 2013)
Leon A Danyel,1 Patrick Schmerler,1 Ludovit Paulis,1–3 Thomas Unger,4 U Muscha Steckelings1,5 1Center for Cardiovascular Research, Institute of Pharmacology, Charité Medical Faculty, Berlin, Germany; 2Institute of Pathophysiology, Faculty of Medicine, Comenius University, Bratislava, Slovak Republic; 3Institute of Normal and Pathological Physiology, Slovak Academy of Sciences, Bratislava, Slovak Republic; 4CARIM, Maastricht University, Maastricht, the Netherlands; 5Institute of Molecular Medicine, Department of Cardiovascular and Renal Physiology, University of Southern Denmark, Odense, Denmark Abstract: The angiotensin type 2 receptor (AT2R) and the receptor MAS are receptors within the renin–angiotensin system, which mediate tissue-protective actions such as anti-inflammation, antifibrosis, and antiapoptosis. In recent years, several programs have been launched in order to develop drugs that act as agonists on the AT2R or MAS to take therapeutic advantage of the protective and regenerative properties of these receptors. This review article will focus on recent data obtained in preclinical animal and in vitro models with new AT2R-agonistic molecules (Compound 21 and β-amino acid substituted angiotensin II) and with relevance for blood pressure (BP) regulation or hypertensive end-organ damage. These data will include studies on vasodilation/vasoconstriction in isolated resistance arteries ex vivo, studies on kidney function, studies on vascular remodeling, and studies that measured the net effect of AT2R stimulation on BP in vivo. Current data indicate that although AT2R stimulation causes vasodilation ex vivo and promotes natriuresis, it does not alter BP levels in vivo acutely – at least as long as there is no additional low-dose blockade of AT1R. However, AT2R stimulation alone is able to attenuate hypertension-induced vascular remodeling and reduce arterial stiffening, which in more chronic settings and together with the natriuretic effect may result in modest lowering of BP. We conclude from these preclinical data that AT2R agonists are not suitable for antihypertensive monotherapy, but that this new future drug class may be beneficial in combination with established antihypertensives for the treatment of hypertension with improved protection from end-organ damage. Keywords: renin–angiotensin system, AT2-receptor, vasodilation, blood pressure, kidney function, vascular remodeling